Severe Growth Deficiency is Associated with STAT5b Mutations that Disrupt Protein Folding and Activity - Varco-Merth, Benjamin (Endocrine Society, 2013)
The first genetic defect in human signal transducer and activator of transcription (STAT)5b was identified in an individual with profound short stature and GH insensitivity, immune dysfunction, and severe pulmonary disease, and was caused by an alanine to proline substitution (A630P) within the Src homology-2 (SH2) domain. STAT5b(A630P) was found to be an inactive transcription factor based on its aberrant folding, diminished solubility, and propensity for aggregation triggered by its misfolded SH2 domain. Here we have characterized the second human STAT5b amino acid substitution mutation in an individual with similar pathophysiological features. This single nucleotide transition, predicted to change phenyalanine 646 to serine (F646S), also maps to the SH2 domain. Like STAT5b(A630P), STAT5b(F646S) is prone to aggregation, as evidenced by its detection in the insoluble fraction of cell extracts, the presence of dimers and higher-order oligomers in the soluble fraction, and formation of insoluble cytoplasmic inclusion bodies in cells. Unlike STAT5b(A630P), which showed minimal GH-induced tyrosine phosphorylation and no transcriptional activity, STAT5b(F646S) became tyrosine phosphorylated after GH treatment and could function as a GH-activated transcription factor, although to a substantially lesser extent than STAT5b(WT). Biochemical characterization demonstrated that the isolated SH2 domain containing the F646S substitution closely resembled the wild-type SH2 domain in secondary structure, but exhibited reduced thermodynamic stability and altered tertiary structure that were intermediate between STAT5b(A630P) and STAT5b(WT). Homology-based structural modeling suggests that the F646S mutation disrupts key hydrophobic interactions and may also distort the phosphopeptide-binding face of the SH2 domain, explaining both the reduced thermodynamic stability and impaired biological activity.